A pragmatic strength and conditioning intervention for firefighters: Feasibility of the Tactical Athlete Resilience Program (TARP). Issue 1 (3rd October 2022) - Sharp, Paul; Caperchione, Cristina M.; Brown, Georgia A.; Stadnyk, Antony; Marin, Elizabeth; Hulin, Billy; Wade, Jarrod; Mott, Brendan; Gabriel, Mark; Impellizzeri, Franco; Fullagar, Hugh H. K.
Abstract: Issue Addressed: Firefighting is physically and mentally taxing and recruits are expected to have optimal health and fitness. However, physical fitness tends to decline following initial training, placing firefighters at an increased risk for stress and injury. Efforts are needed to engage and support firefighters in maintaining adequate health and fitness to withstand the rigorous demands of their occupation. This study examined the feasibility of TARP, a pragmatic strength and conditioning intervention for metropolitan‐based firefighters, delivered in collaboration with a professional National Rugby League club. Methods: A mixed‐methods approach was utilised to examine program implementation, recruitment and sample characteristics, intervention satisfaction and acceptability, and participants' response to the intervention. Evaluation measures included field notes taken during steering committee meetings, participant flow data, baseline and follow‐up outcome measures, self‐report questionnaires, and telephone interviews with a sample of participants. Results: Participants (N = 113) were predominantly men (82%) with a mean age of 43 ± 9.3 years and BMI of 26.6 ± 2.9 kg/m 2 . Program satisfaction was high (95% very satisfied or somewhat satisfied) among program completers (42% retention). Key strengths of the program included delivery through the professional sports club, quality of facilities and equipment, and scheduling flexibility. Future programs should consider incorporating education or training to support behaviour change maintenance and strategies to retain participants at follow‐up. Conclusions: Results provide valuable insights into the design and delivery of interventions for firefighters and demonstrate the importance of strong partnerships between community stakeholders.